POLA ASUH ORANG TUA DALAM MEMBENTUK KARAKTER RELIGIUS ANAK USIA DINI (5-6 TAHUN) DI JORONG PARIT BATU KENAGARIAN LADANG PANJANG KABUPATEN PASAMAN - Indra Arnita; Salmi Wati; Arman Husni; Zulfani Sesmiarni (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the phenomenon of the author’s observations about some parents who give freedom, some expect their children to obey the rules without guidance and direction. There are parents who give a lot of input and direction on what children do, and there are parents who give freedom to children. The type of research is qualitative research or field research. Data collection in this writing the authors obtained through interviews, observation and documentation. The source of this writing data uses the key informants of early childhood parents, supporting informants are early childhood. The data analysis technique that the author uses is data reducation, data presentation, and conclusions, then the data validity technique uses source triangulation. Based on the results of the study, it can be understood that the parenting pattern of parents in shaping religious character in children there are differences in the way parents care for their children, there are parents who give freedom and guidance to children. Parents give a lot of input and direction on what their children do, there are parents who have little time to pay attention to their children’s growth and development and expect their children to obey the rules without any guidance and direction and there are also parents who only provide little emotional support to their children. Factors that influence parents in implementing parenting patterns for their children are the level of parental education, economic status and parental occupation. Keywords: Parenting Style, Religious Character